Heterotrophic Euglenoids from Tropical Northern Thailand - Kritsana Duangjan (2018)
© 2017 Kritsana Duangjan et al., published by De Gruyter Open 2017. Among 45 recorded heterotrophic (colorless) taxa of euglenoids, representatives of the genera Petalomonas F. Stein (12 taxa) and Peranema Dujard. (10 taxa) were abundant and showed high diversity. Less frequently identified were Anisonema Dujard. (3), Astasia Dujard. (1), Dinema Perty (2), Entosiphon F. Stein (1), Heteronema Dujard. (4), Menoidium Perty (2), Notosolenus A. Stokes (6), Ploeotia Dujard. (1), Rhabdomonas Fresen. (1) and Urceolus Mereschk. (2). Thirty of these taxa are reported for the first time from northern Thailand. Short descriptions, biogeographical data and original documentation based on light microscopy of living cells in natural communities are included for each reported taxon.